Internet addiction : a handbook and guide to evaluation and treatment - Young, Kimberly S.; Abreu, Cristiano Nabuco de (Hoboken, NJ : John Wiley & Sons)
"Internet addiction is an emergent disorder in the psychiatric and psychological fields. This book provides a theoretical framework to understand how to define and conceptualize compulsive use of the Internet from a clinical perspective. With various theoretical models from the psychiatric, psychological, communication, and sociological fields, it explores the prevalence of the disorder and the most addictive or problematic online applications, such as online pornography, Internet gambling, and online games. Evidenced-based treatment approaches are provided as well. A must-have for every clinician"--Provided by publisher.